Audiences Respond to Interfaith Dialogue Messages on the Jeda Nulis YouTube Channel in the Context of Indonesian Pluralism - Muhammad Rizki Akbar; Abdul Syukur (Khazanah Theologia, 2024)
Purpose: This study examines audience reception of interfaith dialogue on the YouTube channel Jeda Nulis, particularly the “Indonesia Rumah Bersama” series, to analyze how digital narratives promote religious pluralism and social cohesion in Indonesia. Methodology: The research employed a qualitative digital netnography to collect and analyze hundreds of publicly available comments on selected videos, which were then interpreted through Stuart Hall’s encoding/decoding framework. Findings: The findings reveal that the majority of comments reflected dominant-hegemonic readings that fully accepted the tolerant, reflective, and inclusive messages conveyed in the dialogues. A smaller portion of comments demonstrated negotiated readings, where audiences partly agreed with the messages but adapted them to personal beliefs or cultural traditions, while only a marginal minority expressed oppositional readings that rejected the messages on ideological grounds. These reception patterns indicate that humanistic and narrative-driven communication reduces ideological resistance and fosters more open interfaith engagement in digital spaces. Research Implications: Practically, the findings provide insights for content creators, faith-based organizations, NGOs, and government agencies to design more inclusive digital communication strategies that cultivate intergroup trust. Theoretically, this study advances an audience-centered perspective in religious communication by mapping interpretive positions toward interfaith dialogue in live social media interactions. Originality/Value: Unlike much Indonesian scholarship that predominantly emphasizes discourse production and elite messaging, this article highlights the role of audience reception by integrating digital netnography with Hall’s model to explore how digital publics interpret interfaith narratives.